Empowering Women, Sustaining Enterprises: A Study on the Sustainability Factors of Felda Micro-Businesses - Ahmad, Andik Aidah Nadia; Kamarudin, Khairul Hisyam (Journal of Human Capital Development (JHCD), 2025)
This study examines the sustainability factors influencing micro-enterprises operated by FELDA women entrepreneurs in rural Malaysia. The primary objective is to identify the key determinants affecting the long-term sustainability of these enterprises. Employing a quantitative research design and a snowball sampling technique, data were collected through structured questionnaires from 50 FELDA women entrepreneurs in FELDA Lok Heng, Kota Tinggi, Johor. The survey focused on entrepreneurial characteristics, infrastructure, financial support, and socio-cultural dimensions. Descriptive analysis using mean scores revealed that market access, infrastructure availability, financial assistance, and social roles are pivotal in sustaining rural micro-enterprises. The findings highlight the interdependence of physical and non-physical factors in shaping business resilience and continuity. This study contributes to a deeper understanding of women’s entrepreneurship in rural contexts by emphasizing the importance of integrated development strategies and strengthened support systems for FELDA women entrepreneurs. Ultimately, the study provides insights for policymakers and development agencies seeking to foster inclusive and sustainable rural economic growth through targeted interventions.